How do you do this??

tn= tn-1 + 6
t1 = 0

2 Answers
Feb 22, 2018

This question needs some context. What are you trying to get? What is t? etc.

Feb 22, 2018

I'm assuming this is an arithmetic sequence where

t_n=t_(n-1)+6
t_1=0

This is the recursive formula for an arithmetic sequence:

"General formula:" a_n=a_1+(n-1)*d

"Recursive formula:" a_1,a_n=a_(n-1)+d

to find the n^(th) term, with a_1 as the first term, and d as the common difference.

I don't really know what you want to solve, as you gave me the formula without specifying what to find.